The Role of Explainable AI in the Research Field of AI Ethics - Vainio-Pekka, Heidi; Agbese, Mamia Ori-otse; Jantunen, Marianna; Vakkuri, Ville; Mikkonen, Tommi; Rousi, Rebekah; Abrahamsson, Pekka (Association for Computing Machinery, 2023)
Ethics of Artificial Intelligence (AI) is a growing research field that has emerged in response to the challenges related to AI. Transparency poses a key challenge for implementing AI ethics in practice. One solution to transparency issues is AI systems that can explain their decisions. Explainable AI (XAI) refers to AI systems that are interpretable or understandable to humans. The research fields of AI ethics and XAI lack a common framework and conceptualization. There is no clarity of the field’s depth and versatility. A systematic approach to understanding the corpus is needed. A systematic review offers an opportunity to detect research gaps and focus points. This paper presents the results of a systematic mapping study (SMS) of the research field of the Ethics of AI. The focus is on understanding the role of XAI and how the topic has been studied empirically. An SMS is a tool for performing a repeatable and continuable literature search. This paper contributes to the research field with a Systematic Map that visualizes what, how, when, and why XAI has been studied empirically in the field of AI ethics. The mapping reveals research gaps in the area. Empirical contributions are drawn from the analysis. The contributions are reflected on in regards to theoretical and practical implications. As the scope of the SMS is a broader research area of AI ethics the collected dataset opens possibilities to continue the mapping process in other directions.
Keywords: Explainable AI; AI Ethics; Artificial Intelligence; Systematic Mapping Study; fi=Viestintätieteet|en=Communication Studies|